Relação ensino-pesquisa no exercício da docência: Um caminho de (re)invenção permanente das práticas pedagógicas - Peixeiro, Daniela Conti de Oliveira (Universidade do Vale do Rio dos Sinos, 2018)
This dissertation presents a study about teachers’ education and the education-researching-teaching relationship in a private community school in São Paulo state. The main issue investigated was: “how the teaching-research relationship is / can be present in the school and how to create conditions of possibility to expand it?”. For such purpose, the dissertation was divided into five chapters that address: the relationship between the author’s professional trajectory and her restlessness; previous works addressing the same subject, which may be similar or different from the investigated research object; methodological procedures, considering the focus group as a space for empirical data collection and for continuous education of the teachers who participated in this research; teacher professionalism, considering discussions about the history of teacher’s (un)professionalization, teaching feminization and teaching-related knowledge; the analyzes carried from the material produced in the focal group; and the presentation of the Professional Master's Degree final product. The empirical material of this dissertation was studied from four categories of analysis. They are: teacher training, teaching feminization, teaching practices and teacher-researcher. The final product consists in the construction of a workshop for (re)construction of teaching practices. All the author’s restlessness, researches and problematizations have dialogued with theorists who research about teacher education, such as Antonio Nóvoa (1992, 2001 2002, 2009, 2017), Sandra Mara Corazza (1997 e 2011), Bernadete Gatti (2005), Selma Garrido Pimenta (1996), Menga Lüdke (2001) and Maurice Tardif (2014); as well as authors who are dedicated to studying history of teaching professionalization, teaching feminization and discourses emerging from classroom, among them: Jane Soares de Almeida (1998), Marília Pinto de Carvalho (1999), Marisa Vorraber Costa (2006), Guacira Lopes Louro (1997) and Alfredo Veiga-Neto (2017). Finally, it is intended, after the focus group meetings, that the teachers who were part of this study perceive the school as a place of teacher education and view the research as a way to build knowledge, to review and to reconstruct practices, to question their professionalism, to relate theory and practice, and to critically analyze reality, as well as to discuss how the care practices are seen, how care and femininity are articulated and how mothering is incorporated into the pedagogical doing. It is also intended to make possible that the teaching-researching relationship reinvent new meanings, new movements and encounters of the subjects and the group of subjects, redefining routes that reframe and (re)construct knowledge, practices and feelings. This work also significantly expands my theoretical knowledge, instigating me to think about new questions and questions about teaching practice and knowledge, encouraging me to research more about some aspects that made me astonished and curious, as well as to articulate and narrow my pedagogical practices and my daily activities to research interests.
Keywords: Pesquisa; Formação de professores; Saberes; Práticas; Identidade; Profissionalidade docente; Research; Teacher education; Knowledge; Practices; Identity; Teacher professionalism; ACCNPQ::Ciências Humanas::Educação